Pasteurella multocida Bacteremia in an Immunocompromised Patient - Kukrety, Shweta (Case Rep Med, 2016)
We present the case of a 61-year-old Caucasian gentleman who presented with a one-day history of fever, chills, and altered mental status. His symptoms were initially thought to be secondary to cellulitis. Blood cultures grew Pasteurella multocida, a rare pathogen to cause bacteremia. Our patient was treated with ciprofloxacin for two weeks and made a complete and uneventful recovery. Our patient's uncontrolled diabetes mellitus and chronic kidney disease put him at a higher risk for developing serious P. multocida infection. The patient's dog licking the wounds on his legs was considered as the possible source of infection. As P. multicoda bacteremia is rare, but severe with a high mortality rate, it is imperative to have a high index of suspicion for this infection especially in the vulnerable immunocompromised population.